Application of Bim 5D in The Redesign of Building 2 Hermina Hospital Banyumanik Semarang Using Autodesk Software - Farina Rizka Meidina Putri; Alvira Ayu Febriani; Bambang Setiabudi; Asri Nurdiana (Engineering Faculty, UNSOED, 2026)
The application of 5D-based Building Information Modeling (BIM) method in re-planning Building 2 of Hermina Banyumanik Semarang Hospital to improve the effectiveness and efficiency of construction projects. The methods used include literature studies related to building structure planning guidelines, calculation of dimensions, reinforcement, and loading of lower and upper structures. Furthermore, 3D modeling using Autodesk Revit 2024, structural analysis with Autodesk Robot Structural Analysis Professional (RSAP) 2024, and integration of scheduling and cost estimation through Autodesk Naviswork 2024 and Microsoft Project 2021 were conducted. This process resulted in a re-planning that included the volume of work, project duration, and project cost. The results show that the structural elements were safe according to standards, the project duration is 33 weeks, and the project cost is IDR 40,642,964,000.00 including 11% VAT. The integration of 3D models, schedules, and budgets in BIM 5D provides better visualization and helps anticipate potential delays in project implementation. Thus, the application of BIM 5D can improve stakeholder performance and efficiency in managing building construction projects.